IMMU-36. HIGH AFFINITY CHIMERIC ANTIGEN RECEPTOR WITH CROSS-REACTIVITY TO CLINICALLY-RELEVANT EGFR MUTATED PROTEINS. (9th November 2020) - Thokala, Radhika; Binder, Zev; Yin, Yibo; Milone, Michael; O'Rourke, Donald M
Abstract: Tumor heterogeneity is one of the key reasons for therapeutic failure in Glioblastoma (GBM). Our chimeric antigen receptor (CAR) T cell clinical trial (NCT02209376) against Epidermal growth factor receptor (EGFR) variant III (EGFRvIII) demonstrated successful trafficking of T cells across the blood brain barrier into GBM active tumor sites. However, CART cell infiltration was associated with a selective loss of EGFRvIII+ tumor cells and upregulation of immunosuppressive molecules. Post-CAR T treated tumor specimens showed continued presence of EGFR amplification and oncogenic EGFR extracellular domain (ECD) missense mutations. To study this further We generated two structurally different CARs by fusing the scFv of mAb806 to 4-1BB and Killer immunoglobulin like receptor (KIR) co-stimulatory domains. Both 4-1BB and KIR based EGFR806 CAR T cells specifically lysed tumor cells and secreted cytokines when co-cultured with U87-MG (expressing low levels of EGFR) and U87-MG EGFR (U87-MG transduced with EGFR wild type for amplified background) cell lines and engineered to ectopically express targeted EGFR-ECD missense mutations and EGFRvIII. Unlike EGFR-specific cetuximab based CAR, EGFR-806CART cells did not kill EGFR wild type expressing fetal brain primary astrocytes and keratinocytes in vitro. We further evaluated the in vivo efficacy of 806-CARs and EGFRvIII CART currently in clinic in NSG mice. While EGFRvIII CART cells cleared EGFRvIII+ tumors alone 806 CART cells controlled EGFRvIII, amplified EGFR and EGFRR108K-mutant bearing tumors. KIR-CAR treated tumors are GVHD free and enhanced survival compared to 4-1BB based CARs. The broad specificity of EGFR806 CART cells to amplified EGFR and its mutant variants gives us the potential to clear various forms of EGFR. The enhanced anti-tumor efficacy by KIR based CAR in vivo setting provides us with additional therapeutic options.